2018
DOI: 10.1302/2046-3758.71.bjr-2017-0135.r1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aminoguanidine (AG) and pyridoxamine (PM) on ageing human cortical bone

Abstract: ObjectivesAdvanced glycation end-products (AGEs) are a post-translational modification of collagen that form spontaneously in the skeletal matrix due to the presence of reducing sugars, such as glucose. The accumulation of AGEs leads to collagen cross-linking, which adversely affects bone quality and has been shown to play a major role in fracture risk. Thus, intervening in the formation and accumulation of AGEs may be a viable means of protecting bone quality.MethodsAn in vitro model was used to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Although pyridoxamine is a known inhibitor of AGEs, namely when glucose causes AGE accumulation, we did not investigate whether a higher concentration of pyridoxamine (>50 mM) could prevent the ribose‐related decrease in bound water fraction over 4 weeks. A lower concentration of pyridoxamine (0.1 mM) was found to reduce the accumulation of fluorescent AGEs when human cortical bone was incubated in 0.1 M glucose for 7 days at 50°C . Because ribose is significantly more reactive than glucose and formation of ribose‐protein adducts (ie, AGE precursors) may be sufficient to affect bound water, it is possible that the PM concentration used in our study was not high enough to completely block the Maillard reaction between sugar and protein.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although pyridoxamine is a known inhibitor of AGEs, namely when glucose causes AGE accumulation, we did not investigate whether a higher concentration of pyridoxamine (>50 mM) could prevent the ribose‐related decrease in bound water fraction over 4 weeks. A lower concentration of pyridoxamine (0.1 mM) was found to reduce the accumulation of fluorescent AGEs when human cortical bone was incubated in 0.1 M glucose for 7 days at 50°C . Because ribose is significantly more reactive than glucose and formation of ribose‐protein adducts (ie, AGE precursors) may be sufficient to affect bound water, it is possible that the PM concentration used in our study was not high enough to completely block the Maillard reaction between sugar and protein.…”
Section: Discussionmentioning
confidence: 84%
“…A lower concentration of pyridoxamine (0.1 mM) was found to reduce the accumulation of fluorescent AGEs when human cortical bone was incubated in 0.1 M glucose for 7 days at 50°C. (43) Because ribose is significantly more reactive than glucose and formation of ribose-protein adducts (ie, AGE precursors) may be sufficient to affect bound water, it is possible that the PM concentration used in our study was not high enough to completely block the Maillard reaction between sugar and protein. Lastly, there are inherent limitations in the use of cadaver bone as donor information is limited.…”
Section: Discussionmentioning
confidence: 95%
“…One study found that IDI was correlated with femoral neck strength IDI (r = −0.478), and utilizing aBMD and IDI together in a multivariate model significantly increased the predictive ability of bone strength (r = 0.883) than either measurement alone 51 . BioDent was also capable of monitoring the effects of in vitro aminoguanidine and pyridoxamine incubation on ex vivo bone tissue mechanical behavior 52 . In another application, IDI was used to predict maximum screw torque in fracture fixation 53 .…”
Section: Biodent Studiesmentioning
confidence: 99%
“…Moreover, studies using diabetic animals suggest that increased AGEs are associated with lower bone stiffness and are more susceptible to microcrack propagation compared with non‐diabetic controls, but there is little information regarding crack initiation and propagation due to AGEs in human bone . Further, about 12 studies in human bone focused on studying the effect of non‐enzymatic glycation on cancellous bone mechanical behavior, but only six studies report findings on cortical bone, two of which utilize bovine bone . There is some indication that in diabetes (where AGEs are particularly relevant) cortical bone is the primary bone type affected with a reduced quality .…”
mentioning
confidence: 99%
“…Another study illustrated that an increase in AGEs in human bone was associated with deteriorated reference point indentation properties but not with mechanical properties assessed by 3‐point bending tests . The last study illustrated that certain drug targets can be used to decrease AGEs in human bone with a consequent improvement in cyclic reference point indentation properties . In addition, there are drastic differences in AGE levels across these studies, which makes it even more difficult to compare the findings.…”
mentioning
confidence: 99%